Legal Responsibility Of Notaries In Making Authentic Deeds Based On The Civil Code - Brian Werik; Sriono Sriono; Nimrot Siahaan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
A notary is a public official who is authorized to make authentic deeds in accordance with the provisions of the Notary Law (UUJN). Authentic deeds have perfect evidentiary power as regulated in the Civil Code (KUHPerdata). This study aims to analyze the legal responsibility of notaries in making authentic deeds based on the Civil Code. The research method used is the normative legal method with a statutory approach and case studies. The results of the study indicate that the responsibilities of notaries include civil, criminal, administrative, and professional ethics aspects. Notaries must carry out their duties with full responsibility in order to provide legal certainty for the community.